Societal Development in Rural China - Qian, Wenrong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book provides a broad survey of Chinese rural households, examining ongoing changes in Chinese society and economy through the lens of the situation of rural families in China. Based on data from Zhejiang University's China Rural Household Panel Survey (CRHPS) in 2015 on rural households, which analyses all aspects of grass-roots rural households in China, this volume offers a scientific analysis of social development in rural China, exploring notably the basic structure, employment situation, income and expenditure, social security, and education situation of Chinese rural households, as well as the governance and public services of rural communities.
Part 1 Survey Background and Sampling design -- Introduction -- Survey Sampling Design -- Part 2 Basic Characteristics of Rural Households -- Basic Structure of Rural Households -- Employment of Rural Households -- Income and Expenditure of Rural Households -- Fortune of Rural Households -- Part 3 Public Service of Rural Households -- Social Security of Rural Households -- Education of Rural Households -- Community Environment of Rural Households -- Governance and Public Services of Rural Communities -- Part 4 Research Conclusions -- Conclusions.
Keywords: Sociology, Urban; Sociology; Social groups; Industrial sociology; Urban Sociology; Sociology of Family, Youth and Aging; Sociology of Work